Standards of Personal Protective Equipment in Handling Covid-19 in Nurses - Nour Sriyanah; Esse Puji Pawenrusi; Suradi Efendi (Global Health Science Group, 2022)
Personal Protective Equipment (PPE) is a tool that has the ability to protect a person part or all of the body from potential dangers in the work environment. Personal protective equipment is very important for nurses, every action taken by medical personnel always has a high risk of being exposed to infections, for example when treating a catheter, treating wounds, cleaning body fluids, taking blood, and so on jumlah who has a covid-19 incidence rate, especially nurses in the province of South Sulawesi / Makassar as many as 350 who are exposed. This study aims to determine the standards of Personal Protective Equipment (PPE) for nurses in handling Covid-19 at the Makassar City Hospital. The type of research used in this study was descriptive research, with the sample in this study being nurses at Makassar City Hospital with 54 respondents, the sampling technique used was Accidental Sampling. The results showed that of the 54 respondents, the first step before using PPE respondents who answered checked as many as 18 respondents (33.3%), washing hands 36 respondents (66.7%), steps to use complete PPE and could protect those that could protect as many as 54 respondents (100%), using complete PPE as many as 42 respondents (77.8%) and taking steps to release PPE completely as many as 46 respondents (85%). Respondents who carry out treatment activities and meet directly with patients who have confirmed COVID-19 in the Infection Center room who use complete Personal Protective Equipment (PPE) and in accordance with the direction of health protocols.